2013
DOI: 10.1117/1.oe.52.4.046201
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol modulation transfer function model for passive long-range imaging over a nonuniform atmospheric path

Abstract: An aerosol modulation transfer function (MTF) model is developed to assess the impact of aerosol scattering on passive long-range imaging sensors. The methodology extends from previous work to explicitly address imaging scenarios with a nonuniform distribution of scattering characteristics over the propagation path and incorporates the moderate resolution transfer code database of aerosol cross-section and phase function characteristics in order to provide an empirical foundation for realistic quantitative MTF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Recently, different views of the significance of aerosol MTF have been reported. In ref [6], on the basis of aerosol MTF modeling, it was concluded that "the image impact is almost completely radiometric: the image contrast is reduced uniformly at all spatial frequencies, and there is negligible image blurring". On the other hand, another recent paper [7] claims that aerosols "can have a non-negligible effect on the atmospheric point spread function".…”
Section: Introductionmentioning
confidence: 99%
“…Recently, different views of the significance of aerosol MTF have been reported. In ref [6], on the basis of aerosol MTF modeling, it was concluded that "the image impact is almost completely radiometric: the image contrast is reduced uniformly at all spatial frequencies, and there is negligible image blurring". On the other hand, another recent paper [7] claims that aerosols "can have a non-negligible effect on the atmospheric point spread function".…”
Section: Introductionmentioning
confidence: 99%
“…We used the derived analytic expressions Eqs. (13) and (19) ), there is more degradation in the lower frequencies and less in the high frequencies compared to the Kolmogorov power-law exponent. Whereas 4 α → there is little degradation in the first few frequencies and more in the high frequencies compared to 3 α → .…”
Section: Numerical Resultsmentioning
confidence: 90%
“…From the results we observe that low turbulence brings less degradation on the imaging performance compared with high turbulence strength and this can be deduced directly from Eq. (13). This phenomenon can also be explained as in low turbulence the number of turbulence cells that bring the variation of optical wave phase decreases.…”
Section: Numerical Resultsmentioning
confidence: 91%
See 2 more Smart Citations